An abstract model for parallel execution of prolog - Patinho, Pedro José Grilo Lopes (2017)
Logic programming has been used in a broad range of fields, from artifficial intelligence applications to general purpose applications, with great success. Through its declarative semantics, by making use of logical conjunctions and disjunctions, logic programming languages present two types of implicit parallelism: and-parallelism and or-parallelism. This thesis focuses mainly in Prolog as a logic programming language, bringing out an abstract model for parallel execution of Prolog programs, leveraging the Extended Andorra Model (EAM) proposed by David H.D. Warren, which exploits the implicit parallelism in the programming language. A meta-compiler implementation for an intermediate language for the proposed model is also presented. This work also presents a survey on the state of the art relating to implemented Prolog compilers, either sequential or parallel, along with a walk-through of the current parallel programming frameworks. The main used model for Prolog compiler implementation, the Warren Abstract Machine (WAM) is also analyzed, as well as the WAM’s successor for supporting parallelism, the EAM; Sumário: Um Modelo Abstracto para Execução Paralela de Prolog A programação em lógica tem sido utilizada em diversas áreas, desde aplicações de inteligência artificial até aplicações de uso genérico, com grande sucesso. Pela sua semântica declarativa, fazendo uso de conjunções e disjunções lógicas, as linguagens de programação em lógica possuem dois tipos de paralelismo implícito: ou-paralelismo e e-paralelismo. Esta tese foca-se em particular no Prolog como linguagem de programação em lógica, apresentando um modelo abstracto para a execução paralela de programas em Prolog, partindo do Extended Andorra Model (EAM) proposto por David H.D. Warren, que tira partido do paralelismo implícito na linguagem. É apresentada uma implementação de um meta-compilador para uma linguagem intermédia para o modelo proposto. É feita uma revisão sobre o estado da arte em termos de implementações sequenciais e paralelas de compiladores de Prolog, em conjunto com uma visita pelas linguagens para implementação de sistemas paralelos. É feita uma análise ao modelo principal para implementação de compiladores de Prolog, a Warren Abstract Machine (WAM) e da sua evolução para suportar paralelismo, a EAM.